Tides of empire : religion, development, and environment in Cambodia - Work, Courtney (Asian anthropologies ;, 2020)
"At the forested edge of Cambodia's development frontier, the infrastructures of global development engulf the land and existing social practices like an incoming tide. Cambodia's distinctive history of imperial surge and rupture makes it easier to see the remains of earlier tides, which are embedded in the physical landscape, and also floating about in the solidifying boundaries of religious, economic, and political classifications. Using stories from the hybrid population of settler-farmers, loggers, and soldiers, all cutting new social realities from the water and the land, this book illuminates the contradictions and continuities in what the author suggests is the final tide of empire"--